2005
DOI: 10.1088/0031-9155/50/18/002
|View full text |Cite
|
Sign up to set email alerts
|

The use of megavoltage CT (MVCT) images for dose recomputations

Abstract: Megavoltage CT (MVCT) images of patients are acquired daily on a helical tomotherapy unit (TomoTherapy, Inc., Madison, WI). While these images are used primarily for patient alignment, they can also be used to recalculate the treatment plan for the patient anatomy of the day. The use of MVCT images for dose computations requires a reliable CT number to electron density calibration curve. In this work, we tested the stability of the MVCT numbers by determining the variation of this calibration with spatial arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
128
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(136 citation statements)
references
References 14 publications
7
128
0
1
Order By: Relevance
“…Thomas et al (13) utilized three densities — air, bone, and tissue. This study, and that of Langen et al (18) and Cheung et al, (16) used up to 16 densities. It is noted that although the measured CT–ED calibration curve for MV CBCT was shown in this and other studies to be a linear relationship, as expected theoretically, there are uncertainties which should be understood and may not be detected with a limited number of material densities.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Thomas et al (13) utilized three densities — air, bone, and tissue. This study, and that of Langen et al (18) and Cheung et al, (16) used up to 16 densities. It is noted that although the measured CT–ED calibration curve for MV CBCT was shown in this and other studies to be a linear relationship, as expected theoretically, there are uncertainties which should be understood and may not be detected with a limited number of material densities.…”
Section: Discussionmentioning
confidence: 78%
“…Several papers have presented MV CT–ED calibration 8 , 18 , 23 , 29 , 30 for Tomotherapy, as well as linac‐based systems. Ruchala et al (29) report an “almost perfect” correlation (0.999) between the results obtained at a high dose and a more clinically relevant 7 cGy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pre‐treatment MVCT images are beneficial in that they provide daily image guidance ( 38 ) and allow for calculation of the daily delivered dose. ( 39 ) It has been demonstrated that accurate deformable registration of daily MVCT and planning CT images permits the evaluation of accumulated dose distributions delivered over the coarse of treatment. ( 9 ) Planning CT (256×256×91 (median) voxels; 1.9×1.9×3.0 mm3) images were acquired on a PQ 5000 system.…”
Section: Methodsmentioning
confidence: 99%